Self-Management Education for Improving Self-care Behaviours in People with Diabetes: An Evidence Based Systematic Review - Mega Safitri, Rizki; Syahrizal, Rofi; Mahyuvi, Tata (Rifa'Institute, 2025)
Introduction: Diabetes mellitus (DM) is a chronic condition requiring effective self-care to prevent complications. However, many patients struggle with self-care due to limited health literacy, inadequate resources, and socio-cultural barriers. Objective: This systematic review examined the effectiveness of Diabetes Self-Management Education (DSME) interventions in improving self-care, glycemic control, and quality of life for individuals with type 2 diabetes. Methods: Following PRISMA guidelines, a search across multiple databases (2018-2025) identified 12 eligible experimental or quasi-experimental studies. The results consistently demonstrated that DSME significantly improved diabetes outcomes. Result and Discussion: Participants showed enhanced self-efficacy, dietary adherence, self-care behaviors, and glycemic control (HbA1c reductions of 0.6% to 1.1%). Quality of life also improved, with some studies reporting a 7.2-fold increase in the likelihood of better health-related quality of life among DSME participants. Furthermore, innovative and contextually adapted delivery methods, such as SMS, booklets, and culturally specific models like “PASTI SEMBUH,” proved highly feasible and acceptable, particularly in resource-limited settings. Conclusion: DSME is a powerful, evidence-based intervention In conclusion, DSME is a powerful, evidence-based intervention that improves clinical outcomes, quality of life, and self-care capacity in individuals with type 2 diabetes. Integrating diverse and contextually relevant DSME methods into national health strategies, especially in low- and middle-income countries, is crucial for wider reach and effectiveness.